2023
DOI: 10.1002/anie.202301440
|View full text |Cite
|
Sign up to set email alerts
|

Study of Intermolecular Reconfiguration of Flexible COF‐5 Film and Its Ultra‐high Chemiresistive Humidity Sensitivity

Abstract: Recently, abundant active materials are developed to achieve the wearable detection of human body humidity. However, the limited response signal and sensitivity restrict further application due to their moderate affinity to water. Herein, we propose a flexible COF‐5 film synthesized by a brief vapor‐assisted method at room temperature. Intermediates are calculated by DFT simulation to investigate the interaction between COF‐5 and water. The adsorption and desorption of water molecule result in a reversible def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Figures a and S8 display the hydrophobic property of CsPbI 3 PQD films without and with Cs 2 PbI 2 Cl 2 NS modification. With the increasing Cs 2 PbI 2 Cl 2 NS concentration, the contact angle of the PQD film increases from 84.3° (hydrophilic) to 100.8° (hydrophobic), confirming the enhanced hydrophobicity of the PQD film surface due to the modification of Cs 2 PbI 2 Cl 2 NSs. , As H 2 O and O 2 in the atmosphere could easily combine with ionic vacancies on the PQD surface, a series of reactions occur under light stimulation, resulting in the phase transition and degradation of PQDs . The excessive vacancy on the PQD surface and the poor hydrophobicity of the PQD solid film will accelerate the occurrence of this adverse reaction.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Figures a and S8 display the hydrophobic property of CsPbI 3 PQD films without and with Cs 2 PbI 2 Cl 2 NS modification. With the increasing Cs 2 PbI 2 Cl 2 NS concentration, the contact angle of the PQD film increases from 84.3° (hydrophilic) to 100.8° (hydrophobic), confirming the enhanced hydrophobicity of the PQD film surface due to the modification of Cs 2 PbI 2 Cl 2 NSs. , As H 2 O and O 2 in the atmosphere could easily combine with ionic vacancies on the PQD surface, a series of reactions occur under light stimulation, resulting in the phase transition and degradation of PQDs . The excessive vacancy on the PQD surface and the poor hydrophobicity of the PQD solid film will accelerate the occurrence of this adverse reaction.…”
Section: Resultsmentioning
confidence: 73%
“…Figures 5a and S8 NSs. 51,52 As H 2 O and O 2 in the atmosphere could easily combine with ionic vacancies on the PQD surface, a series of reactions occur under light stimulation, resulting in the phase transition and degradation of PQDs. 53 The excessive vacancy on the PQD surface and the poor hydrophobicity of the PQD solid film will accelerate the occurrence of this adverse reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Fathoming this need for the COF-based chemiresistive gas sensors, Mei et al fabricated a flexible and robust COF-5 film on a polyimide (PI) substrate and employed it for humidity sensing. 325…”
Section: Chemiresistive Gas Sensing Of Porous Materialsmentioning
confidence: 99%
“…[34] By combination the active sites and large surface area, impedance type humidity sensors based on COFs have been fabricated basing on the Grotthuss chain reaction [35] and ion transport. [36] The most recent studies demonstrated the reversible protonated tautomerism mechanism [29] and the intermolecular reconfiguration feature [37] in the humidity sensing behavior, promoting a significant humidity sensitivity in the resistance type sensors. [37] In terms of gas sensing process, the sensitivity to analyte molecules is highly related to the organic building units and linkage of COFs.…”
Section: Intermolecular Interactionmentioning
confidence: 99%